1977
DOI: 10.1159/000225204
|View full text |Cite
|
Sign up to set email alerts
|

5α-Reductase as a Target Enzyme for Anti-Prostatic Drugs in Organ Culture

Abstract: Short-term organ culture of rat and human prostatic tissues has been utilized as a means of testing drugs potentially useful in cancer of the prostate. Optimal conditions, particularly the concentration of T, have been established for organ culture of such tissues and the effects of various drugs on 5α-reductase activity (5α-RA) have been utilized as a means of ascertaining antiprostatic actions of the various compounds and drugs tested. Thus, it was shown that estracyt, estradiol-17β, progesterone, and novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Organ culture of prostatic tissue was performed as described previously (Kadohama et al 1977). Explants (2 mm3) prepared from ventral and dorsolateral lobes of prostates were maintained in culture for 7 days in me¬ dium 199 containing varying concentrations of T (0-1.0 pM) and Oe2 (0-0.1 pM).…”
Section: B) In Vitro Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organ culture of prostatic tissue was performed as described previously (Kadohama et al 1977). Explants (2 mm3) prepared from ventral and dorsolateral lobes of prostates were maintained in culture for 7 days in me¬ dium 199 containing varying concentrations of T (0-1.0 pM) and Oe2 (0-0.1 pM).…”
Section: B) In Vitro Experimentsmentioning
confidence: 99%
“…This is in agreement with a previous report on the influence of Oe2 treatment on 5a-reductase activity (Fencle & Villee 1973;Yamanaka et al 1975). Oe2 is a known strong inhibitor of 5ct-reduction of T in vitro (Lee et al 1973;Kadohama et al 1977), butin the castrated animal this type of inhibition may not be of importance. In contrast to the findings of Leav et al (1971) that Oe2 administration to dogs leads to a shift from reductive to oxidative meta¬ bolism of T, we observed some inhibition of I7ß-hydroxy oxidation of T in Oe2-treated rats.…”
Section: )mentioning
confidence: 99%
“…For more than a decade, the writing has been on the wall that human prostate cancer depends on DHT and not T for hormonal support (see, eg, Kadohama et al [49]). Unfortunately, this hypothesis could not be verified experimentally, as methods for eliminating or lowering DHT levels within the prostate were not available.…”
Section: The Dht Hypothesis Of Prostate Cancermentioning
confidence: 99%
“…Apart from culture media and methodology, the design of an organ culture experiment is also multifaceted and, as yet, there is not a standardized procedure. In particular, the time of testosterone addition is variable as some investigators delay the introduction of testosterone for 24 hours to deplete the explants of endogenous androgens [26,27], while others only add testosterone on the first day of the culture [ 131. Yet Lasnitzki [ 11 concluded that testosterone should be renewed every second day to maintain effective hormone levels.…”
Section: Testosterone Concentrations Ranging From Lo-' Tomentioning
confidence: 99%